Pediatric pulmonologists’ current practices and variations in flexible bronchoscopy: a national survey study from Türkiye - Ocak, Ece; Başaran, Erdem; Çakır, Erkan; Çobanoğlu, Nazan; Ergenekon, Pınar; Eryılmaz Polat, Sanem; Girit, Saniye; Kartal Öztürk, Gökçen; Kılınç, Ayşe Ayzıt; Köse, Mehmet; Özdemir, Ali; Özsezen, Beste; et al. (The Turkish Journal of Pediatrics, 2026)
Background. Flexible bronchoscopy (FB) is a critical diagnostic and therapeutic tool in respiratory diseases, enabling airway assessment, sample collection, and therapeutic interventions. Despite international guidelines, practices vary widely across centers. This study aimed to assess current FB practices and to identify variations among pediatric pulmonologists in Türkiye. Methods. A descriptive cross-sectional survey was distributed via email to clinical directors of 19 centers performing FB in March 2023. The survey comprised 80 questions across seven domains: demographics, patient preparation, bronchoscopy procedure, sedation/anesthesia, discharge, bronchoscope cleaning, and respondent comments. Participants were asked to provide accurate and objective data on FB practices at their centers. Results. All 19 centers participated in the survey, achieving a 100% response rate. The median FB experience was 12.5 years (IQR: 1-30), with a median 210 procedures per year per center (min-max: 30-500; IQR: 80-250). The most frequently reported indications were atelectasis (84.2%), bronchiectasis (78.9%), suspected foreign body aspiration (52.6%), and to obtain bronchoalveolar lavage (BAL) in patients with immunodeficiency (52.6%). Nine centers (47.4%) indicated performing advanced bronchoscopic procedures, including endobronchial biopsy (31.6%), bronchoscopic intubations (26.3%), and tracheal/bronchial stent insertion (10.5%). General anesthesia (84.2%) was the predominant sedation method, and propofol (89.5%) the most frequently used agent. Premedication was used in 13 centers (68.4%), with midazolam being the most commonly used agent (76.9%). Twelve centers (63.2%) also used topical lidocaine for local anesthesia. Respondents reported the need for developing interventional procedures and increasing the number of trained bronchoscopy teams. Conclusions. This first comprehensive national survey of pediatric FB practices in Türkiye, encompassing all relevant centers, revealed significant heterogeneity in procedural approaches, particularly regarding sedation protocols, BAL techniques, and interventional capabilities. The findings underscore the importance of developing interventional procedures and enhancing the training of pediatric pulmonologists and interdisciplinary teams practicing pediatric bronchoscopy to improve patient outcomes and procedural consistency.